The Janus-faced City: A Sensory History of the London Blitz 1940–1941 - Antinkaapo, Erika (My University, 2016)
The city of London was, during the years of 1940–1941, a city under fire. The metropolis seemed to have two faces, like the Roman deity Janus: the face of the daylight hours, so normal, and yet so deceiving in its false quietness – and at nightfall, the city turned, and the face of it was the face of the devil himself, transforming London into a living inferno. This thesis examines the sensescapes of the Blitz, through the diaries and memoirs written of that time. The primary sources consist of seven different diaries, two autobiographies, and four research volumes that contain multiple diary- and memoire entries, mostly from the Mass Observation Archives and from the Imperial War Museum. The sensory approach is a new orientation in the field of history – it studies the five senses in their cultural contexts, interpreting the often subtle ways in which the senses affect into society, politics, culture, and class hierarchies, to name only but few. The subject of the sensory history of war is a theme widely unexamined: this thesis contributes to this frontier field by unveiling the sensorium of the London bombings, comparing the differences between the halves of nychtemeron, and examining how the Blitz was communicated by the writers as a lived, bodily experience. This study reveals the very different sensory worlds in which the Londoners lived, during a time that is often described with the mythical solidarity that was thought to exist between the people. The reality of the homeless, working class, and poor were in the foul smelling tubes, poor law -dated rations, and in the smoking ruins of East End – the contrast was massive reflecting it to the luxury hotels and restaurants of the upper classes, opportunities for evacuation, sheltering possibilities, and overall comforts of life.